Waḥdat al-Wujūd in The Perspective of Shāh Walī Allāh Al-Dihlawī - Rifqi Miftahul Amili (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2024)
This article aims to analyze the thought of Shāh Walī Allāh al-Dihlawī as a Sufi who accepted the doctrine of waḥdat al-wujūd, and reinterpreted it philosophically. This research confirms that the idea of sufism of Shāh Walī Allāh al-Dihlawī cannot be separated from the falsafi style. This research uses a hermeneutic approach, which is a method used to uncover the meaning of writings that become primary and secondary sources, as well as understand various kinds of facts. The primary data sources of this research are the main works of Shāh Walī Allāh al-Dihlawī which are related to his sufism ideas. Primary data is supported by authoritative secondary data, of course, which is related to his tasawwuf thought. The findings in this study are that Shāh Walī Allāh al-Dihlawī asserts that Ibn ‘Arabi’s pantheistic union with God is an experiential, and not an ontological reality (union with the divine form). Waḥdat al-wujūd, ontologically, that the only Ultimate Being is God, other than Him is a relative or contingent being. This Ultimate Being benefits the contingent being through wujūd al-munbasiṭ, which is the first emanation of the Ultimate Being. From this wujūd al-munbasiṭ will give rise to other forms (maujūdāt). On that basis, nature was created through God’s tajallī